An efficient approach of face detection and recognition from digital images for modern security and office hour attendance system - Anik, Md. Kamrul Islam (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.